Gram's Song - Henley, Karyn; Farnsworth, Bill (Wheaton, Ill. : Tyndale House Publishers, 2003)
Anthony enjoys spending time with his grandmother, so when she dies he is sad until his mother tells him that Gram is now with Jesus, and reminds him of the treasures she left him, including her special song.
Accelerated Reader AR